Photodegradation of ethylene/propylene/polar monomers co- and terpolymers. I - Prepared by group 4 catalyst systems - Fernandes, Susete N.; Correia, Sandra; Prasad, A. V.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Marques, Maria M.; Singh, R. P. (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
The photooxidative degradation behavior of polyethylene, its copolymers (propylene/polar monomers) and terpolymers, synthesized by a group 4 catalyst system, has been studied by Fourier transform infrared spectroscopy and confirmed with scanning elecrton microscopy for morphological changes. The kinetics of photodegradation has also been studied. Surface damage caused by polychromatic (>= 290 nm) at 55 degrees C in air is presented in different micrographs. The rate of photodegradation is very fast in terpolymers containing polar monomers as compared with copolymers and polyethylene. Morphological study of these photodegraded samples showed a very good relation with photodegradation results.
Keywords: functional polyolefins; Photodegradation; UV irradiation

Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Photo-stabilization of EPDM-clay nanocomposites: effect of antioxidant on the preparation and durability - Lonkar, Sunil P.; Kumar, A. Pratheep; Singh, Raj Pal (Polymers for Advanced Technologies, 2007)
The present study is to examine the photo-stabilization effect of an antioxidant on the photo-oxidation of ethylene-propylene-diene monomer (EPDM)-clay nanocomposites. During the preparation of EPDM-clay nanocomposites via melt processing antioxidants are usually incorporated along with clay, which allows phenolic antioxidant molecules to get adsorbed onto acidic clay platelets and their interaction with metallic impurities reduces the stabilizing efficiency of the antioxidant. The nanocomposites were obtained by solution dispersion followed by melt compounding of EPDM and organophilic montmorillonite (OMMT). The samples were characterized by conventional tools such as X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, and thermo-gravimetric analysis (TGA). It was found, upon photo-irradiation (lambda > 290 nm) studies by following the changes in functional groups and surface morphology, that photo-degradation was lowered by the antioxidant and the efficiency of the antioxidant could be improved by initial incorporation of antioxidant in the EPDM matrix. In EPDM-clay nanocomposites, a stabilizing activity of the antioxidant was observed above some threshold concentration of the antioxidant. The relationship between the nanoclay reinforcement and stabilizing efficiency in terms of photo-oxidation and surface morphology for their applicability are discussed. The methodology adopted for this study is also justified through our observation. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: ethylene-propylene-diene monomer; nanocomposites photo-degradation antioxidant and stabilization

Isothermal crystallization and melting behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Singh, R. P. (Thermochimica Acta, 2009)
The effect of layered double hydroxide (LDH) nanolayers on the crystallization behavior of polypropylene (PP) was studied based on the preparation of nanocomposites by a melt intercalation method. The isothermal crystallization kinetics and subsequent melting behavior of PP/LDH hybrids were studied with differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). Studies revealed that the LDH promoted heterogeneous nucleation, accelerating the crystallization of PR The Avrami equation successfully describes the isothermal crystallization kinetics of PP/LDH hybrids and signifies heterogeneous nucleation in crystal growth of PR The varying values of Avrami exponent (n) and half crystallization time (t(1/2)) of PP and PP/LDH hybrids describes overall crystallization behavior. The crystallite size (D(hkl)) and distribution of different crystallites in PP varied in presence of LDH. A significant increase in melting temperature is observed for PP/LDH hybrids. The POM showed that smaller and less perfect crystals were formed in nanocomposites because of molecular interaction between PP chains and LDH. The value of fold surface free energy (sigma(e)) of PP chains decreased with increasing LDH content. Finally, the overall results signify that LDH at nanometer level acted as nucleating agent and accelerate the overall crystallization process of PR (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Isothermal crystallization; Layered double hydroxide; Melting behavior; Polypropylene nanocomposites

Preparation and nonisothermal crystallization behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Morlat-Therias, Sandrine; Caperaa, N.; Leroux, Fabrice; Gardette, Jean Luc; Singh, R. P. (Polymer, 2009)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared via melt intercalation using dodecyl sulfate anion modified LDH and maleated PP as compatibilizing agent. Evidently the interlayer anions in LDH galleries react with maleic anhydride groups of PP-g-MA and lead to a finer dispersion of individual LDH layers in the PP matrix. The nanostructure was characterized by XRD and TEM; the examinations confirmed the nanocomposite formation with exfoliated/intercalated layered double hydroxides well distributed in the PP matrix. The nonisothermal crystallization behavior of resulting nanocomposites was extensively studied using differential scanning calorimetry (DSC) technique at various cooling rates. In nonisothermal crystallization kinetics, the Ozawa approach failed to describe the crystallization behavior of nanocomposites, whereas the Avrami analysis and Jeziorny method well define the crystallization behavior of PP/LDH nanocomposite. Combined Avrami and Ozawa analysis (Liu model) also found useful. The results revealed that very small amounts of LDH (1%) could accelerate the crystallization process relative to the pure PP and increase in the crystallization rates was attributed to the nucleating effect of the nanoparticles. Polarized optical microscopy (POM) observations also support the DSC results. The effective crystallization activation energy was estimated as a function of the relative degree of crystallinity using the isoconversional analysis. Overall, results indicated that the LDH particles in nanometer size might act as nucleating agent and distinctly change the type of nucleation, growth and geometry of PP crystals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Layered double hydroxide; Nonisothermal crystallization kinetics; Polypropylene nanocomposites

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers

Thermal, mechanical, and rheological characterization of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer Engineering and Science, 2012)
Polypropylene (PP)/organomodified layered double hydroxide (LDH) nanocomposites were prepared in order to examine the influence of LDH content on thermal, mechanical, and rheological properties. The nanostructure examinations by X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the exfoliated/intercalated dispersion of LDH. Incorporation of the LDH resulted in a noteworthy improvement in the thermal stability of PP. It was shown that the addition of LDH contributed to the reinforcement effect by increasing the elastic modulus. The mechanical performance, as evaluated by stressstrain curves, reveal that PP/LDH hybrid materials showed significant contribution toward increment in elastic modulus, tensile strength but at the expense of impact strength. The rheological response showed a strong influence of LDH particles on the flow behavior of the PP/LDH melt which resulted in enhancement of storage, loss of moduli, and complex viscosity of nanocomposites. Therefore, the nanocomposites have higher moduli but better processibility compared with pure PP. Overall, the results indicated that the LDH particles in nanometer size might act as potential reinforcing agent for polypropylene. POLYM. ENG. SCI., 52:20062014, 2012. (c) 2012 Society of Plastics Engineers

Morphology, polymorphism, and metal ion adsorption studies of electrospun nanofibers based on pvdf and organically modified layered double hydroxide - Birajdar, Mallinath S.; Wanjale, Santosh D.; Lonkar, Sunil P. (Journal of Applied Polymer Science, 2013)
Nonwoven nanofiber mats of polyvinylidene fluoride (PVDF) with modified layered double hydroxide (MLDH) were prepared by electrospinning. The fiber morphology was studied using scanning electron microscopy. X-ray diffraction and FTIR spectroscopy was used to characterize the polymorphism in electrospun mats. Fibers of diameter in the range 80-800 nm with beads of about 2-3 mu m size were observed for pure PVDF, while in case of PVDF/MLDH nanocomposites the number and size of beads were found to be significantly reduced. Uniform and fine nanofibers were obtained at lower content of MLDH, but slightly rough surface was seen for higher content. FTIR and X-ray diffraction patterns signify various crystalline forms of electrospun PVDF. The content of polar -crystalline phase of PVDF, which exhibit piezo and ferroelectric properties was found to be enhanced significantly due to reinforcement of MLDH. Use of these nanofiber mats for heavy metal Cu (II) removal was explored. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4508-4515, 2013
Keywords: Adsorption; electrospinning; fibers